Kokomo: The History and Meaning of a Remarkable and Elusive Place Name. (3rd April 2018) - McCafferty, Michael
Abstract : "Kokomo", the name of a small city in central Indiana, was originally a personal name of a historical Miami Indian man. Although the correct translation of the man's name was published in the 1800s, it was soon forgotten. Ever since then the name has defied interpretation because it was garbled to opacity. On the way to explaining the name's form and meaning, based on early historical spellings, this article will describe the impressive trajectory that the life of "Kokomo" has taken for approximately two centuries, from an Algonquian language personal name to American slang.